The Role of Education in Promoting Social Innovation Processes in the Society - Surikova, Svetlana; Oganisjana, Karine; Grinberga-Zalite, Gunta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The purpose of the paper is to clarify the role of education in promoting social innovation processes in the society based on the main findings of the theoretical study conducted from October 2014 to January 2015 within the project “Involvement of the Society in Social Innovation for Providing Sustainable Development of Latvia” supported by the National Research Program 5.2. EKOSOC-LV. The paper provides the analysis of causal interaction between social innovation and education, as well as two conceptual models which disclose the relationship between social innovation and education and the triple role of education in promoting social innovation; both are elaborated by the authors.